Webtoon sebagai Inovasi Media Pembelajaran Sejarah Kebudayaan Islam untuk Meningkatkan Motivasi Belajar Siswa Kelas V Madrasah Ibtidaiya - Moh Ali Fauzi; Luluk Indarinul Mufidah (STAI Miftahul Ula Nganjuk, 2025)
This research aims to develop, test the validity, and evaluate the effectiveness of Webtoon as an innovative learning medium for Islamic Cultural History subject, specifically on the